A new preclinical model of western diet‐induced progression of non‐alcoholic steatohepatitis to hepatocellular carcinoma. Issue 7 (31st May 2022) - Green, Christopher D.; Weigel, Cynthia; Brown, Ryan D. R.; Bedossa, Pierre; Dozmorov, Mikhail; Sanyal, Arun J.; Spiegel, Sarah
Abstract: Non‐alcoholic steatohepatitis (NASH) results from the accumulation of excessive liver lipids leading to hepatocellular injury, inflammation, and fibrosis that greatly increase the risk for hepatocellular carcinoma (HCC). Despite the well‐characterized clinical and histological pathology for NASH‐driven HCC in humans, its etiology remains unclear and there is a deficiency in pre‐clinical models that recapitulate the progression of the human disease. Therefore, we developed a new mouse model amenable to genetic manipulations and gene targeting that mimics the gradual NASH to HCC progression observed in humans. C57BL/6NJ mice were fed a Western high‐fat diet and sugar water (HFD/SW) and monitored for effects on metabolism, liver histology, tumor development, and liver transcriptome for up to 54 weeks. Chronic HFD/SW feeding led to significantly increased weight gain, serum and liver lipid levels, liver injury, and glucose intolerance. Hepatic pathology progressed and mice developed hepatocellular ballooning, inflammation, and worse fibrosis was apparent at 16 weeks, greatly increased through 32 weeks, and remained elevated at 54 weeks. Importantly, hepatocellular cancer spontaneously developed in 75% of mice on HFD/SW, half of which were HCC, whereas none of the mice on the chow diet developed HCC. Chronic HFD/SW induced molecular markers of de novo lipogenesis, endoplasmic reticulum stress, inflammation, and accumulation of p62, all of which also participate in the human pathology. Moreover, transcriptome analysis revealed activation of HCC‐related genes and signatures associated with poor prognosis of human HCC. Overall, we have identified a new preclinical model that recapitulates known hallmarks of NASH‐driven HCC that can be utilized for future molecular mechanistic studies of this disease.